KONSEP DESAIN EKOLOGIS RUANG TERBUKA HIJAU DI SUDIRMAN CENTRAL BUSINESS DISTRICT (SCBD) SEBAGAI HABITAT BURUNG - Andi Gunawan; Setia Permana (TATALOKA, 2018)
Landscape in Central Business District (CBD) is part of urban green spaces which have a role to enhance ecological value of the city, one of them is Sudirman Central Business Distict. The existence of birds will strengthen the ecological functions of the city. The aim of this study is to design the green spaces as bird habitat. Lot 17 SCBD has the potential to be developed as a bird sanctuary protection area divided into two areas: nesting and transition area. The method that will be used for this research is descriptive analysis through site survey and literature. The concept that used is eco-friendly bird park, a park that is able to present the directly or indirectly interaction between humans and birds without reducing the fulfillment of ecological functions of the park. The design concept applies the deco art style that has a dynamic impression and a pliable flexible shape. The dynamic impression will be applied in the form of arches on the park patterns and circulations to create natural impression. The existence of Lot 17 park can soften the surrounding condition, which is a storey building. Visitors can observe birds on tree canopies using binoculars that is placed on the deck view and canopy tree rail.